Strategi Pengembangan Komoditas Pangan Unggulan dalam Menunjang Ketahanan Pangan Wilayah (Studi Kasus di Kabupaten Batang, Propinsi Jawa Tengah) - Wijaya, Oki (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
Food is considered as one strategic issues in Indonesia in the reason that food expenditure reached 58.81 percent of total household expenditure in 2014. Therefore, increasing food security and agribusiness development should be main program in agricultural and region development. One thing that can be done to improve food security and agribusiness development area is the development of comparative advantage of regional food commodities. This study aims to (i) identify the comparative advantage of food commodities; and (ii) develop alternative strategy in the development of comparative advantage of food commodities. The study was conducted in Batang Regency, Central Java Province. The method used in this study was Location Quotient (LQ), External Factor Evaluation Matrix (EFE), Internal Factor Evaluation (IFE), Matrix Strength Weaknesses Opportunities Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM). The results showed that food commodities which are has comparative advantage in Batang Regency are rice, corn, and cassava. Strategic priority for the development of comparative advantage of food commodities is the utilization of Appropriate Technology Service Post (POSYANTEK), for the settlement of food commodities problems. The strategy is expected to increase productivity of food crops and support food security, especially on the availability of food.